Pengaruh Penggunaan Media Pembelajaran Flipbook Ekoraya terhadap Hasil Belajar Siswa pada Materi Keanekaragaman Hayati Kelas di V SDN 007 Samarinda Ulu - Ranti Febrian; Khusnul Khotimah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning media play an important role in helping students understand learning materials in a more engaging and meaningful way. The use of Flipbook Ekoraya as a learning medium is an instructional innovation that can improve students’ motivation and learning outcomes. This research was conducted due to the low learning outcomes of fifth-grade students at SD Negeri 007 Samarinda Ulu in IPAS learning on Biodiversity material. The aim of this study was to determine the effect of using Flipbook Ekoraya learning media on students’ learning outcomes. This study employed a quantitative approach with a Quasi Experimental method using a Nonequivalent Control Group Design. The population consisted of 81 fifth-grade students, with class V B as the control group and class V D as the experimental group. Data were collected through observation, tests, and documentation using Pretest and Posttest instruments. Data analysis included normality test, homogeneity test, T-Test, and N-gain. The results showed a Sig. (2-tailed) value of 0.020 (< 0.05), indicating that Flipbook Ekoraya significantly affects students’ learning outcomes.